Spitz Nevus Intermingling With a Hemangioma. (October 2016) - Fernandez-Flores, Angel; Saeb-Lima, Marcela
Abstract : Abstract: We report on a Spitz nevus intermingling with a hemangioma in the same biopsy from the right thigh of a 10-year-old boy. The hemangioma was made of dilated vessels in superficial areas but of narrow and angulated vessels in the deep and lateral zones. The Spitz nevus was typical, showing maturation, and no worrisome cytological features. The immunohistochemical study demonstrated expression by the vascular component of CD31, CD34, factor VIII-related antigen, and Wilms tumor 1, whereas the vessels did not express D2-40 human herpes virus 8 or glucose transporter-1. The melanocytic component expressed HMB-45 (weakly and mainly in the superficial zones), Melan-A and S-100 protein. A perivascular continuous layer of pericytes expressing smooth muscle actin was also evident.